REPRESENTASI NILAI PERJUANGAN DALAM NOVEL BERHENTI DI KAMU KARYA GIA PRATAMA - Hadi Rumadi (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2020)
Background of this research is about life struggle in the novel entitled Berhenti di Kamu (#BERHENTIDIKAMU) by Gia Pratama. Values ​​are general guidelines to direct human action refer to good and wrong based on the rules to act according to the rules, whether in religion, moral, or social reflecting the beauty and harmony. The research problem is how to represent the value of the main character's struggle in the novel Berhenti di Kamu. The research aims to describe the importance ​​of the battle of life in the novel Berhenti di Kamu. This research's benefit is developing educational theory, especially the idea of values for giving appreciation to the literary works full of life values. This research method is qualitative research. The analysis shows that the importance ​​of struggle is not only physical fighting but also intrapersonal fighting or fighting. Berhenti di Kamu by Gia Pratama explores the internal conflict, which makes the reader perceives the indirect moral lesson. The value of struggle is the outcome of a human's efforts in undergoing the experience, challenges, and problems in life. The importance ​​of conflicts illustrates how big a person's struggle in their life. Human life is inseparable from the human battle itself.